THE ROLE OF INTEGRATED SERVICE POST CADRES IN THE JAVANESE COUNTRYSIDE - Diah Fatma Sjoraida; cucu sugyati (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2018)
This study seeks to make a deep, systematic analysis of the urgency of implementing elements in the implementation of public health policies, especially in the field of mother and child in West Java, Indonesia. This study is important in order to evaluate whether the government services on maternal and child health is sufficient or not. With descriptive-qualitative method this study presents a discussion of how the implementers interact with the community implementing public health programs in West Java province so that their presence is indispensable. With theories of implementation of policies and interactionism, the data was obtained and it showed that (a) the unity of the coordination and uniformity of information services, and a network of cooperation in public health institutions, in the Provincial Government of West Java have been performed well; (b) in implementing their obligations the implementers are highly motivated for the services of public health has become a major function in the duties and functions of the health department. However, the lack of health care workers who directly addressing maternal and child health were perceived by the public so well that this study recommend the convening of additional health workers in the community.